Academic Writing in the University. Systematic Mapping of Academic Research in Costa Rica - Godínez Rojas, Laura Paulette (2024)
Written production is one of the most concerning issues regarding the skill development of the student population at all levels. However, research on related topics, both in student writing samples and in other samples of written and spoken language, remains limited and has little or no impact on the didactics and assessment of this skill in teaching practice. Therefore, it is relevant to review the studies currently conducted in the country, based on the publications of this century, to answer the question of how academic writing has continued to be approached in Costa Rica and determine if there are any changes with respect to the situation of the previous century. At the same time, this systematic review of academic sources enables an analysis of their approaches, objectives, proposals, and conclusions. The 21st century represents a paradigm shift, as Carlos Sanchez takes up the proposals of Rodino, Ross, and Vincenzi, who were the only authors offering a nontraditional vision in the last century. Since then, the contribution of most of the new researchers has followed the direction of these pioneers, which augurs a promising future for academic production and, hopefully, for the teaching of writing in Costa Rica. These studies indicate a pressing need to change how this subject is taught in this country.